Green Energy Technology - Chen, Wei-Hsin; Ong, Hwai; Ho, Shih-Hsin; Show, Pau Loke (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book, entitled "The Green Energy Technology", covers technologies, products, equipment, and devices, as well as energy services, based on software and data protected by patents and/or trademarks. The recent trends underline the principles of a circular economy such as sustainable product design, extending the product's lifecycle, reusability, and recycling. These are highly related to climate change and environmental impact, and limited natural resources require scientific research and novel technical solutions. This book will serve as a collection of the latest scientific and technological approaches to "green"-i.e., environmentally friendly and sustainable-technologies. While the focus is on energy and bioenergy, it also covers "green" solutions in all aspects of industrial engineering. Green Energy Technology addresses researchers, advanced students, technical consultants and decision-makers in industries and politics. This book is a comprehensive overview and in-depth technical research paper addressing recent progress in Green Energy Technology. We hope that readers will enjoy reading this book.